METASTATIC HAEMANGIOPERICYTOMA: A RARE VARIETY OF SOFT TISSUE SARCOMA PRIMARILY INVOLVING THE LEFT GLUTEAL MUSCLES: Metastatic Haemangiopericytoma - Awan, Maj Muhammad Younus; Shukr, Irfan (Pakistan Armed Forces Medical Journal, 2012)
Haemangiopericytomas have been reported in almost all anatomic sites, but the tumours reported in the extremities or in the intramuscular locations with atypical histological features and malignant behaviour, are rare1. Tumours involving the extremities, pelvis, head and neck, back, retroperitoneum and abdomen have been reported previously2,3,4. Haemangiopericytoma are a variety of soft tissue sarcomas which are vascular in origin and consist of pericytes5. Malignancy in haemangiopericytoma is predicted from large tumour size, presence of necrosis, increased cellularity and over 4 mitosis per high power fields suggested by Enzinger and Smith6. However, tumour behaviour and the occurrence of distant metastasis may clinically be the only way to confirm the malignant nature of the tumour. Metastasis or local recurrence may take several years to develop7